Will Effect of Self-Efficacy on Performance With Discipline as a Mediating Variable - Indra Kusdarianto; Muh. Yusuf Qamaruddin; Burhanuddin Harahap; Ilham Tahier (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Performance refers to the level of employee input towards the advancement and growth of the organization or company in which they are employed. Performance can also be defined as an analysis of the tasks performed by employees concerning pre-established criteria. The study aimed to examine and analyze the impact of self-efficacy as a mediator in discipline on the performance of employees at the Palopo City Regional Revenue Office (BAPENDA)Purpose: The research methodology used is quantitative study. This study is conducted by employees’ human resource management theory (HRM) at BAPENDA Palopo City to examine the impact of self-efficacy on employee performance, with work discipline acting as an intermediary factor.Design/methodology/approach: The approach used in this study is associative; the research sample was 156 employee civil servants at BAPENDA Palopo City, and the main data was obtained via a Likert-scale survey instrument, data analysis technique with PLS SEM using SmartPLS program, data was collected by administering a questionnaire with structure to the respondents.Findings/Results: Research results indicate that self-efficacy significantly and positively influences employee performance at BAPENDA Palopo City, confirming its importance as a key psychological factor in enhancing work outcomes. However, self-efficacy does not significantly influence work discipline, work discipline does not significantly affect employee performance, mediate work discipline relationship between self-efficacy and performance does not significantly influence. Conclusion: These findings indicate that optimal employee performance in public sector organizations depends not only on individual confidence but also on actual competence, organizational systems, and managerial practices. Therefore, self-efficacy alone is not sufficient to foster disciplined behavior or improve performance indirectly through discipline.Originality/value (State of the art): This would make it possible to evaluate the performance of employees in terms of self-development and employee discipline in order to improve the maximum amount of service that is provided to the community. Keywords: employee performance, management planning, human resources, plan's effectiveness, work discipline